R, Rancangan Dan Implementasi SPK Evaluasi Kinerja Instruktur Menggunakan Metode TOPSIS PT.Robonico Berbasis Web: Rancangan dan Implementasi Metode TOPSIS Untuk Mengukur Kinerja Instruktur PT. ROBONICO Indonesia Berbasis WEB - Nawafih, Wendy Asswan Cahyadi, Deni Muharam (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2024)
Instructor performance evaluation can be built with a decision support system so that the assessment process can be carried out measurably and systematically. The TOPSIS method is used to perform calculations in the system and this method is effective and suitable in conducting multi-criteria assessments based on several previous studies. The problems faced by the company are related to the improvement of instructor competence and discipline as well as responsibility for the Standard Operating Procedures that have been set by the company. Previous evaluation programs were ineffective and efficient in addressing instructor performance assessment issues. This study designs and implements a decision support system with the TOPSIS method to deal with problems related to instructor performance evaluation at Pt. Robonico Indonesia. Thus, the Instructor Performance Evaluation Decision Support System using the TOPSIS Method can effectively solve assessment problems, can be efficient when conducting assessments.